MENGEMBANGKAN KEUNGGULAN KOMPETITIF DALAM PASAR YANG BERGEJOLAK - Sansaloni Butar Butar (Universitas Katolik Soegijapranata Semarang, 2016)
Doing business today is not the same as doing business a few decades ago. Unpredictable market together with constantly changing consumersdesire contribute to heightening competition among business enterprises. Big profit are no longer easy to attain. Firms Life cycles are becoming increasingly shorter. Corporate bankruptcies are very common and inreased at unprecedented rate. These are main characteristic of business conditions at present time. The question is how can company survive in such a competitive market? This paper attempts to tackle the question by describing the crucial and important concepts to sharpen firmscompetitive edge. The emphasis in this paper is to describe ways to develop core competencies and strategies based on knowledge gained from firmslong history. The term knowledge (tacit knowledge) refers to the insights gained from the organizational learning process that gives enligtment to all organization members.